Manejo de ventilación mecánica y su implicancia en pacientes adultos con trauma craneoencefálico en el Hospital General de Babahoyo periodo mayo-septiembre 2019 - Moreira Sarcos, Suany Alicia (2019)
Our theme was Management of Mechanical Ventilation and its implication in adult patients with craniocerebral trauma at the General Hospital of Babahoyo during the period May - September 2019. This project was carried out at the Babahoyo General Hospital with 65 patients who had cranioencephalic trauma, which considered a high rate of hospital care due to severe head trauma (TBI) which he considered as an important indicator of mortality and disability throughout the The world being the most common cause of death from closed trauma and mechanical ventilation was undoubtedly the most widely used technique for the management of critical patients, being responsible in many cases for the survival of a large number of patients. The objective was to determine the implication of mechanical ventilation in patients with craniocerebral trauma at the General Hospital of Babahoyo period May-September 2019, from which a great achievement was obtained, the synthetic analytical Inductive-Deductive methods were applied, with qualitative modality. -quantitative, cross-sectional, non-experimental, prospective in a population of 65 patients whose data were taken from the clinical sheet and from the Traumatology area of the Babahoyo General Hospital, we conducted the respiratory therapy staff surveys to learn more about patients with TBI who entered during the established period. There was a predominance of the male sex with 71% over the female sex with 29%. Also the people who suffered these TCE in terms of weight were between 71 to 80kg. The most common cause of these craniocerebral traumas were traffic accidents with 60%. In conclusion of this research project, we obtained good results in terms of the established objectives. Mechanical ventilation was the most used technique in CT, and its application was conditioned to the evaluation of the Glasgow scale, hypoxia being the most frequent complication that There were, as 80% of the professionals surveyed assured. We help raise public awareness about the importance of head trauma and its causes and risk factors.